Getting there, getting by, getting through the UPCB survival handbook. - University of the Philippines. College Baguio (Baguio City Board of Student Services and the Public Information and Publications Office, UP College Baguio, 1993)
Intended for the incoming students of the University of the Philippines-College of Baguio. It aims to help the students find their way around, introduce them to the world of UPCB and to help them through the freshmen year.
A handbook that serves as a guide or survival kit for freshmen students, transferees and visitors of U.P. College Baguio.
Cover title.
Photocopy.
Keywords: University of the Philippines. -- College Baguio; College student orientation -- Philippines -- Baguio City; Student assistance programs -- Philippines -- Baguio City